Mitigating stock price crash risk through accounting conservatism: A French market perspective with competitive contexts - Abdelwahed, Selma (International journal of economic perspectives, 2025)
This research explores the relationship between accounting conservatism and stock price crash risk, with a particular focus on the moderating role of product market competition. Using a sample of 311 non-financial French companies listed on the Paris Stock Exchange within the CAC All Shares index from 2009 to 2020, we employ panel data regression models to examine this dynamic. The study finds a significant negative relationship between accounting conservatism and stock price crash risk, indicating that more conservative accounting practices tend to mitigate the likelihood of extreme stock price drops. Furthermore, this negative association is amplified in environments characterized by high product market competition. This suggests that when firms face intense competition, the protective effect of conservatism on stock price stability becomes more pronounced. By extending existing research, which primarily focuses on the American market, this study provides new insights within the context of France—a civil law country with different legal and regulatory frameworks. The findings have practical implications for managers, encouraging them to adopt conservative accounting practices and enhance transparency to reduce stock price crash risk. Investors can also leverage these insights to make more informed decisions, considering the influence of accounting policies and market competition on stock volatility.